Incidencia del transporte informal en las posturas competitivas y tácticas operativas de las empresas formales de transporte de carga terrestre en la provincia de Manabi 2014 - 2015 - Moreira Macías, María Fernanda (2017)
In the province of Manabí are counted the formal companies of cargo transport, many ofthem considered already traditional, with little capital of operation and with few units, companies that have felt strongly the entrance of companies of Guayaquil and Quito that to have no agencies In Manabí they make trips with load from their origin andthey return with what they find, giving away the cost of the freight since they come with their costs and utilities already covered. Companies such as SERVIENTREGA and ENETSA are formal companies that maintain agencies in Manabí, generating work and trustin clients, as well as investing in the province. The objective of this study was to analyze informal transport and its impact on competitive positions and operational tactics of formal land transport companies, identifying and analyzing each one of them to determine and evaluate the positions and tactics that companies Formal approaches to combat informality, suggesting that informal cargo transport directly influences the competitive and tactical positions of the formal land cargo transport companies in Manabí. It was used as a methodology, first descriptive, then analytical, to arrive at a deductive that allowed us after tabulating the results of the data obtained through the interviews and surveys, to represent them in statistical tables through which it was established the conclusions and recommendations that The research will contribute to the development of the sector.